Peripheral Odontogenic Fibroma A case report - Silva Infantes, Manuel (2008)
The Odontogenic Peripheral Fibroma is the most frequent form of Odontogenic Fibromas and seems to come from the superficial gingival epithelium or dental lamina residuals that remain in an extra bone location. The epithelial component resembles the dental lamina during the early stages of the odontogenesis. Although it has predilection for children and young adults, it can be presented in any age. It is most often observed in women than men.